PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS - Muh. Rezky; Ramly Ramly; Muhammad Saleh (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2020)
Problems of Learning Indonesian Based on Text. This study aims to: (1) explore methodological problems in the implementation of Indonesian language learning, (2) explore cultural problems in the implementation of Indonesian language learning, and (3) explore social problems in the implementation of Indonesian language learning. This research is a qualitative descriptive study. Data collection is done by observation, documentation, and interviews. The results of this study show that teachers have problematic Indonesian language learning with 2013 Curriculum texts in implementing learning, namely: (1) problematic in the delivery of learning material, interaction with students, quality of advice and infrastructure, and preparation of learning tools; (2) problems in responding or perceiving the character of a teacher and student, helping students' self-confidence, and coaching students; and (3) problems in the form of a harmonious relationship with students and between students, building motivation and concentration, helping students to save and measure learning outcomes, to the process of guidance and student habits in learning.